2013
DOI: 10.1103/physrevlett.110.078301
|View full text |Cite
|
Sign up to set email alerts
|

Order-Disorder Transition and Alignment Dynamics of a Block Copolymer Under High Magnetic Fields byIn SituX-Ray Scattering

Abstract: We examine the influence of magnetic fields on the order-disorder transition (ODT) in a liquid crystalline block copolymer. This is motivated by a desire to understand the dynamics of microstructure alignment during field annealing as potentially dictated by selective destabilization of nonaligned material. Temperature resolved scattering across the ODT and time-resolved measurements during isothermal field annealing at sub-ODT temperatures were performed in situ. Strongly textured mesophases resulted in each … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 34 publications
(47 reference statements)
3
69
1
3
Order By: Relevance
“…LC orientation affects the microdomain orientation because of the anchoring of mesogenic units on the microdomain interface. Side‐chain (SC) LC segments repel amorphous segments to form microdomains and stretch the backbone perpendicular to the interface accompanied by arrangement of the mesogens in the SCs parallel to the interface . A magnetic field can align amorphous microcylinders as well as the LC director of the matrix along the field direction throughout the specimen .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LC orientation affects the microdomain orientation because of the anchoring of mesogenic units on the microdomain interface. Side‐chain (SC) LC segments repel amorphous segments to form microdomains and stretch the backbone perpendicular to the interface accompanied by arrangement of the mesogens in the SCs parallel to the interface . A magnetic field can align amorphous microcylinders as well as the LC director of the matrix along the field direction throughout the specimen .…”
Section: Introductionmentioning
confidence: 99%
“…Side‐chain (SC) LC segments repel amorphous segments to form microdomains and stretch the backbone perpendicular to the interface accompanied by arrangement of the mesogens in the SCs parallel to the interface . A magnetic field can align amorphous microcylinders as well as the LC director of the matrix along the field direction throughout the specimen . Smectic (Sm) LCs under shear flow arrange the director in either the velocity gradient or in neutral directions; thus, the microcylinders immersed in an Sm LC matrix compromise on their orientation, arranging their long axis in either the velocity‐gradient or neutral directions even though shear flows usually arrange microcylinders parallel to the flow direction .…”
Section: Introductionmentioning
confidence: 99%
“…Many potential applications for photonic crystals, lithographic templates and engineered membranes are limited by nanoscale defects and disorder in the self-assembled morphologies of BCPs3. The phase separation of BCPs results in different local densities, degrees of crystallinity and chemical environments for specific functional groups between the centre and interface of a polymer block domain.…”
mentioning
confidence: 99%
“…This alignment of domains is observed experimentally for rodcoil copolymers. [24][25][26][27] Micro-phase morphology transformations under an external field were also observed in coil-coil copolymers. [53][54][55][56][57] In particular, the self-consistent mean field calculations reported by Ly et al 53 showed a possible gyroidto-cylindrical micelles transformation of a diblock copolymer melt resulting from the application of an electric field.…”
Section: Resultsmentioning
confidence: 86%
“…This led to alignment of the interfaces perpendicular to the field lines and long range order of a 10 nm lengthscale. Gopinadhan et al 25,26 have reported the controlled rotation of lamellar and cylindrical microdomains of in poly(ethylene oxide-b-6-(40cyanobiphenyl-4-yloxy) hexyl methacrylate) block copolymer using a 6 T magnetic field. For the lamellar layers, the interfaces align along the applied field while the smectic layers are perpendicular to the field.…”
Section: Introductionmentioning
confidence: 99%